Von Willebrand gene tracking by single-tube automated fluorescent analysis of four short tandem repeat polymorphisms - Vidal, Francisco; Julià, Antoni; Altisent, Carme; Puig, Lluís; Gallardo, Dominique (Thrombosis and Haemostasis, 2005)
Molecular diagnosis of von Willebrand disease (VWD) has been hampered by the large size and complex genomic characteristics of the gene involved. For this reason, indirect methods using in-tragenic polymorphic markers described along the von Wille-brand factor (VWF) gene are valuable tools for gene monitoring and linkage analysis. Several studies have demonstrated the four commonly utilized short tandem repeats (STRs), three located in intron 40 and one in the promoter region of the VWF gene, to be highly informative for this task. Our objective was to develop a rapid, automated method to simultaneously analyze these four STRs for VWF gene tracking. Amplification of the four loci is achieved in a single multiplex fluorescent PCR which is then analyzed in the same run by capillary electrophoresis. Data processing with Gene Scan and Genotyper software has simplified management and tabulation of the resulting haplotypes. Analysis of the VWF gene in DNA from 102 individuals (204 chromosomes) revealed that the three STRs within intron 40 showed significant linkage disequilibrium against each other but not against the VWP locus. Moreover, the combination of the four markers offers a high heterozygosity rate (>99%) that improves tracing VWF gene inheritance. In conclusion, the automated fluorescent capillary electrophoresis method presented here is an extremely rapid, simple and highly informative technique for association studies between VWD and the VWF gene in addition to genetic counseling and prenatal diagnosis by precise linkage analysis in VWD-affected families.
Keywords: Short tandem repeats; VNTR; von Willebrand disease; von Wille-brand factor; molecular diagnosis